2014
DOI: 10.1371/journal.pone.0093475
|View full text |Cite
|
Sign up to set email alerts
|

Latent Period and Transmission of “Candidatus Liberibacter solanacearum” by the Potato Psyllid Bactericera cockerelli (Hemiptera: Triozidae)

Abstract: “Candidatus Liberibacter solanacearum” (Lso) is an economically important pathogen of solanaceous crops and the putative causal agent of zebra chip disease of potato (Solanum tuberosum L.). This pathogen is transmitted to solanaceous species by the potato psyllid, Bactericera cockerelli (Šulc), but many aspects of the acquisition and transmission processes have yet to be elucidated. The present study was conducted to assess the interacting effects of acquisition access period, incubation period, and host plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 29 publications
(46 reference statements)
7
51
0
Order By: Relevance
“…Finally, in this Lso-psyllid interaction, it is possible that longer latency periods than normal are required for the replication of Lso in the psyllid body, which provides another explanation for the absence of transmission. However, we did not test for latency periods in B. tremblayi , and the only reported latency period for Lso is in B. cockerelli 29; therefore, additional research is recommended to fully understand the Lso infection process in this psyllid species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in this Lso-psyllid interaction, it is possible that longer latency periods than normal are required for the replication of Lso in the psyllid body, which provides another explanation for the absence of transmission. However, we did not test for latency periods in B. tremblayi , and the only reported latency period for Lso is in B. cockerelli 29; therefore, additional research is recommended to fully understand the Lso infection process in this psyllid species.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of transmission could be explained by different factors. For example, it has been reported that when Lso is acquired, the bacteria must pass through the insect midgut epithelium to infect the haemolymph and then enter the salivary glands1529. It is uncertain if Lso is able to complete circulation in the body of B. tremblayi since this process has not been studied in this psyllid species.…”
Section: Discussionmentioning
confidence: 99%
“…Current experimental evidence suggests that Lso is transmitted in a propagative-circulative manner, which means the bacteria replicate in their vectors and are inoculated in saliva secreted before phloem ingestion (Sandanayaka et al, 2014;Sengoda et al, 2014Cicero et al, 2016a;Mustafa et al, 2015). Previous reports have shown that Lso could be successfully inoculated in a single salivation event in a phloem sieve element by B. cockerelli (Mustafa et al 2015); Thus, it is likely that only small titres of bacteria inoculated are needed to achieve infection.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that when Lso is acquired, the bacteria must pass through the insect midgut epithelium to infect the haemolymph and then enter the salivary glands (Cicero et al, 2016ab;Sengoda et al, 2014). It is uncertain if Lso is able to complete circulation in the body of B. tremblayi since this process has not been studied in this psyllid species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation